Catholic Schools in Latin America and the Caribbean: Enrollment Trends, Market Shares, and Comparative Advantage - Quentin Wodon (Universidad de Navarra, 2019)
The Catholic Church estimates that nine million children were enrolled in K12 Catholic schools in Latin America and the Caribbean in 2016. How has the number of students in Catholic schools evolved over the last two decades? In which countries is enrollment larger, whether in absolute terms or in terms of market share? Are Catholic schools performing better than other schools once controls are introduced for the students that enroll in Catholic schools? Finally, what can be learned from the practices of well-performing schools such as those managed by the Fe y Alegría network? To answer these questions, this paper provides trends in enrollment in Catholic schools in the region, estimates their market share, and discusses lessons from the literature with a focus on Fe y Alegría schools.